Like cattle and horses : nationalism and labor in Shanghai, 1895-1927 - Smith, S. A. (Stephen Anthony), 1952- (Comparative and international working-class history., 2002)
Using journalistic accounts, memoirs, police documents and more, Steve Smith argues that nationalism had a greater hold on working-class identity than class consciousness amongst Shanghai workers from the late-19th century to 1927.